Strategic Development of Sustainable Tourism: Integrating Traveler Preferences of Geopark Ciletuh Through OTA – A Conjoint Analysis Approach - Anatasia, Velly; Budianto, Very; Kamila, Ahya Radiatul; Malini, Lamtiar Hema; Welly, Jocelyn (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2026)
This study investigates the strategic development of sustainable tourism at the Ciletuh Geopark, focusing on how traveler preferences are integrated through Online Travel Agents (OTAs) using a conjoint analysis approach. The research emphasizes the role of OTAs in promoting ecotourism, specifically at the Ciletuh Geopark, a UNESCO Global Geopark located in West Java, Indonesia. The study identifies key attributes of tourism products and OTA features that influence tourists' decisions to visit Ciletuh, including price transparency, competitive pricing, and comprehensive destination information. It also highlights the significance of physical adventure activities, such as trekking, and the natural beauty of Ciletuh's landscapes, particularly its waterfalls, as major factors driving visitor interest. Additionally, the study reveals that infrastructure, such as diverse accommodation options, is essential for enhancing the overall tourist experience and attracting repeat visits. The findings of this study provide valuable insights for tourism managers, local governments, and OTAs, particularly in terms of optimizing marketing strategies, improving tourist engagement, and promoting the sustainable management of the geopark. Furthermore, the research aligns with current trends in digital marketing, which leverage technology to engage tourists, build relationships, and foster loyalty. Overall, this study contributes to the growing body of knowledge on ecotourism and sustainable tourism practices, offering practical recommendations for enhancing the promotion and management of the Ciletuh Geopark as a top-tier tourist destination.